MBRS-15. MELK INHIBITION AS A POTENTIAL THERAPEUTIC STRATEGY AGAINST ALL MOLECULAR SUBTYPES OF MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Ho, Jia-Min; Lim, Zhi-Han; Karthik, Sekar; Su, Jack M; Lin, Qi; Du, YuChen; Shen, Jianhe; Chow, Wing-Yuk; Lau, Ching C; Adekunle, Adesina; Major, Angela; Tarek Elghetany, M; et al.
Abstract: BACKGROUND: Medulloblastoma (MB) is the most common malignant embryonal brain tumors found among children. We found Maternal Embryonic Leucine Zipper Kinase (MELK), an oncogenic serine/threonine protein kinase, capable of disrupting critical cell cycle checkpoints leading to uncontrolled tumor growth, overexpressed among almost all patient tumors for MB. AIM: Our aim was to investigate the role of MELK in tumor biology in primary MB, to exploit its potential as a therapeutic target. RESULTS: We discovered consistently high expression of MELK across different molecular subtypes of patient embryonal MB, highlighting MELK inhibition as an attractive therapeutic strategy across all subtypes of MB. A panel of 5 MB cell lines tested demonstrated variation in MELK mRNA expression. MELK inhibition using a molecular inhibitor OTSSP167 at 50nM concentration in vitro effectively inhibited all except one patient-derived tumor cell lines tested. At 5nM OTSSP167 concentration, proliferation of high MELK-expressing tumor cell lines was effectively inhibited and demonstrated dose-dependent and time-dependent inhibition, but not low MELK-expressing tumor cell lines. We have developed a panel of patient-derived orthotopic xenograft models for MB comprising all 4 subtypes of MB. We demonstrated that MELK expression was retained and expressed on patient xenograft tumors. CONCLUSIONS: MELK inhibition is a potential therapeutic strategy against MB. Further, MELK is an attractive target because it is highly expressed across various molecular subtypes of MB. This study is ongoing to determine in vivo anti-tumor effects of MELK inhibition in MB.